New insight into the enhanced visible light photocatalytic activity over boron-doped reduced graphene oxide. Issue 16 (21st November 2014) - Tang, Zi-Rong; Zhang, Yanhui; Zhang, Nan; Xu, Yi-Jun
Abstract : The B-doped RGO prepared by a facile one-step reflux method exhibits significantly higher visible-light-driven photocatalytic activity than non-doped RGO for the degradation of dyes. Abstract : Boron-doped reduced graphene oxide (B-RGO) synthesized by a facile one-step reflux route is able to exhibit significantly higher photocatalytic activity than non-doped RGO under visible light irradiation. New insights accounting for this photocatalytic activity improvement are discussed, which is distinctly different from the case of B-RGO nanoribbons under UV light irradiation.